Болоњскиот образовен концепт и земјите во транзиција - Донев, Дејан (Conrad-Adenauer-Stiftung, 2011)
From 1999, with the Act of signing Bologna declaration (as a project which is very important for the countries in transition and development in their process of European integration), the universities are in condition of reorganization for the purpose of creating European space for higher education (EHEA) based on the principles of international cooperation and academic exchange which are attractive for European students and academic personnel, and as for the students and personnel from other parts of the world... Even declarative, previous sounds too good to be truth, honest, and from it real! What this article trying "sober" to present is the attempt to look on the other side of this process, which, in countries in transition and development that are trying to be "beloved" somewhere by someone took Bologna uncritically by the copy-paste principle as a new philosophy of education, as a new Bible - incarnates in disrespecting the cultural specifics of the space in which the very same declaration is applying, futher more disrespecting humanistic aims of education. The final stage in questioning that this article places, is the dillema: Do and how much we need once again to find a new posibble alternatives, e.g. the necessity exsistence of conection between Truth, Ethics and Virtue - because the praxis from "Bologna" and its ECT system right now shows that the freedom of learning, creativity and imagination will or are the first victims of its own disciplinary process and driving into its desirable model.
Bologna’s educational concept and countries in transition
Keywords: образовен концепт, Болоња, етика на образование, земји во транзиција